Preparation of nano-selenium from chestnut polysaccharide and characterization of its antioxidant activity - Wang, Shanshan; Wu, Hao; Zhang, Xiaoshuang; Luo, Shihong; Zhou, Shuang; Fan, Haiyan; Lv, Chunmao (Frontiers in Nutrition, 2023)
Chestnut is widely cultivated and has high nutritional value due to its richness in polysaccharides. In order to improve the antioxidant activity of chestnut polysaccharide, chestnut polysaccharide (CP) was extracted by ultrasonic-assisted water extraction and alcohol precipitation and purified by cellulose DEAE-52 exchange and Sephadex G-100 chromatography in this study. CP isolates were characterized by I2-KI reaction, three-strand helical structure analysis, infrared spectrum analysis, and nuclear magnetic resonance detection. The results showed that CP is a pyrylan sugar with triple helical structure and connected by α-glycosidic bonds, with sugar residues 1,4-α-D-Glcp, 1,6-α-D-Galp, 1,5-α-L-Araf, 1,4-α-L-Rhap, and 1,4-β-D-Glcp in the CP backbone. After purification, the branching structure, rod, and spherical structure were significantly increased, with reduced lamellar structure. The in vitro scavenging rates of CP at 10 mg·mL-1 against DPPH, hydroxyl radicals, and ABTS were 88.95 %, 41.38 %, and 48.16 %, respectively. The DPPH free radical scavenging rate of purified polysaccharide fraction CP-1a was slightly enhanced, and the other rates showed a small decrease. Selenized chestnut polysaccharide (CP-Se) was prepared using nano-selenium method. The selenization method was optimized and stable Se-CP was obtained. When the concentration was 5 mg·mL-1, Se-CP had significantly higher scavenging abilities 89.81±2.33 %, 58.50±1.60 %, and 40.66±1.91 % for DPPH, hydroxyl radical, and ABTS radicals, respectively, than those of CP. The results of this study provide insight into the effects purification and selenization of chestnut polysaccharide on antioxidant activity, and also provide a theoretical basis for the development of chestnut polysaccharide for use in functional foods or health products.